Taurine Rescues Cisplatin-Induced Muscle Atrophy In Vitro: A Morphological Study. (13th May 2014) - Stacchiotti, Alessandra; Rovetta, Francesca; Ferroni, Matteo; Corsetti, Giovanni; Lavazza, Antonio; Sberveglieri, Giorgio; Aleo, Maria Francesca
Abstract : Cisplatin (CisPt) is a widely used chemotherapeutic drug whose side effects include muscle weakness and cachexia. Here we analysed CisPt-induced atrophy in C2C12 myotubes by a multidisciplinary morphological approach, focusing on the onset and progression of autophagy, a protective cellular process that, when excessively activated, may trigger protein hypercatabolism and atrophy in skeletal muscle. To visualize autophagy we used confocal and transmission electron microscopy at different times of treatment and doses of CisPt. Moreover we evaluated the effects of taurine, a cytoprotective beta-amino acid able to counteract oxidative stress, apoptosis, and endoplasmic reticulum stress in different tissues and organs. Our microscopic results indicate that autophagy occurs very early in 50  μ M CisPt challenged myotubes (4 h–8 h) before overt atrophy but it persists even at 24 h, when several autophagic vesicles, damaged mitochondria, and sarcoplasmic blebbings engulf the sarcoplasm. Differently, 25 mM taurine pretreatment rescues the majority of myotubes size upon 50  μ M CisPt at 24 h. Taurine appears to counteract atrophy by restoring regular microtubular apparatus and mitochondria and reducing the overload and the localization of autophagolysosomes. Such a promising taurine action in preventing atrophy needs further molecular and biochemical studies to best define its impact on muscle homeostasis and the maintenance of an adequate skeletal mass in vivo.